On Intersectionality: Decolonization, Inclusion, and Diversity-focused Pedagogies - Joelle Nagle (Canadian Society for Studies in Education, 2017)
The focus of this Special Issue (English) is to divert attention from the insidious global discourses centered on the re-assertion of white dominance through anti-immigration policies, and shift the conversation to one centered on the important work being done in graduate educational research that acknowledge our history and reflects on our role(s) in the continued treatment of Indigenous peoples and people of colour within Canada. This is with the aim to engage in anti-oppressive pedagogies that not only envisage reconciliation, but that consider action towards reconciliation. This is evidenced through a discourse analysis of the First Nation, Métis, and Inuit Education Policy Framework in Ontario (Currie-Patterson & Watson), a quanti-qualitative study on racism and reverse racism with teachers in Alberta (Lorenz), an exploration of the historical and contemporary impacts of racism on children of colour in our schools (Brady), and the examination of the Truth and Reconciliation Commission of Canada's First Report and the consideration of a context-responsive pedagogical framework for an education for reconciliation (Siemens).